The Life and Death of a Protest Anthem at the Frontier of a New Cold War - Janny HC Leung (Law Text Culture, 2020)
Amidst the rise of a new Cold War between China and the US, Hong Kong has been called Ground Zero, the new Berlin, or the Global Frontier by various media outlets. During an ongoing US-China trade war, the Water Movement broke out in 2019. It was the largest and most prolonged social movement that Hong Kong has seen, and one that was met with the direst consequence – the imposition of a sweeping National Security Law that has changed the political landscape of Hong Kong. Soon after the social movement erupted, the song Glory to Hong Kong gained huge popularity and came to be known unofficially as the ‘national anthem’ of Hong Kong. It has been sung regularly at protests, with many language versions being circulated on YouTube. Taking a social semiotic approach, this paper interprets the meaning of this protest anthem, teasing out its multimodal layers and analysing its production, lyrics, musical form, digital renditions, and live performances in light of the evolving socio-political situation at the time. The analysis suggests that certain renditions of the song expressed not only political defiance but also a budding national imagination as a route of redressing injustice, as disappointment in rule of law grew; however, ideological cohesion among movement participants remained limited. Although the National Security Law has successfully quenched such political expressions, confidence in the rule of law has to be restored in order to provide a much-needed pressure valve for Hong Kong.